Interpretation of the Verbal Similarities according to Sheikh Al-Shaarawi he Died In 1998 AD in his Interpretation of Al-Khawatir from Verses (58-59) of Surat Al-Baqarah- Graphic study - Ashour, Hoda Hamad Naeema; Al-Falahi, Issa Ahmed Mahal (Journal of Ecohumanism, 2024)
It is necessary for every researcher before delving into the heart of a topicHAnd its details from Summary in it he explains the approach he followed in arranging his issues. Therefore, it was necessary to classify and divide the issues either according to their occurrence in the Qur’an, or according to their classification according to the type of verbal analogy to which they belong. It is no secret that each approach has its drawbacks and advantages. And the terminology, and therefore I will strive to follow a unified curriculum unless I notice that, or I find benefit from diversifying the curricula, and all of that I will discuss matter.